COMPUTATIONAL THINKING AS A STRATEGY FOR ELICITATION REQUIREMENTS IN DOCUMENTS - Reis, Helena Macedo; Tostes, Maria Fernanda do Prado; Biserra, Carolina; Tiosso, Fernando; de Souza, Rodrigo Clemente Thom (Revista Interface Tecnológica, 2020)
Requirements elicitation is the first step of requirements engineering with the objective of seeking, surveying, elaborating, negotiating, specifying and verifying the services and restrictions of a system. There are several techniques for eliciting requirements, including document analysis. Despite the advantages of elicitation through document analysis, there are some restrictions, such as the lack of data integration and difficulty in detailing the information. To minimize these problems, this study investigated the use of Computational Thinking to support requirements gathering. To verify the proposed strategy, the elicited requirements were validated by four evaluators through the Requirements Review and a Prototype. The results showed that the evaluators considered that the requirements were adequately elicited for the development of applications to support the perioperative post-surgical processes for nursing.
Keywords: Applied Computing; Interactive Learning Environments; Software Engineering; Requirements Analysis